Echoes of the Metellus Balearicus propaganda - Pedroni, Luigi (Gerión. Revista de Historia Antigua, 2012)
According to Servius, the monster Geryon would have ruled over the Balearic Islands. This version of the myth seems more recent than the one dating back to Hesiod, according to which Geryon occupied only the island called Erytheia. The reason and the circumstances of the birth of this version are not clear. Traces of it can be found in other ancient authors. It is noteworthy that in Livy the myth of Geryon is narrated in connection with the Roman conquest of the Balearic Islands. This version of the myth could be present originally in the works of Cecilius Metellus Numidicus, who was in exile with Elius Stilo, teacher of Varro. Alternatively, it is possible to attribute the introduction of it to Cornelius Balbus the younger, grandson of L. Cornelius Balbus of Gades, who fought in Spain under the command of Metellus Pius. It is likely, therefore, that the replacement of Erytheia with the Balearic Islands in the myth of Hercules and Geryon may be attributed to the propaganda of Metellus Balearicus, who triumphed over the pirates in 121 BC.
Keywords: Geryon; Balearic Islands; Metellus Balearicus; Cornelius Balbus.